2013
DOI: 10.1021/ol4001922
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Oxidative Insertion of Carbon Monoxide to N-Sulfonyl-2-aminobiaryls through C–H Bond Activation: Access to Bioactive Phenanthridinone Derivatives in One Pot

Abstract: Palladium-catalyzed oxidative carbonylation of N-sulfonyl-2-aminobiaryls through C-H bond activation and C-C, C-N bond formation under TFA-free and milder conditions has been developed. The reaction tolerates a variety of substrates and provides biologically important phenanthridinone derivatives in yields up to 94%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(34 citation statements)
references
References 65 publications
0
33
0
1
Order By: Relevance
“…General synthetic approaches rely on metal‐assisted catalysis, such as Pd,,, Ni, or Cu catalysts, organic mediators, radical initiators, or photocatalysis‐employing Ir‐complexes . These routes are accompanied by severe disadvantages such as harsh conditions, the necessity for additives or complex ligands, leastwise stoichiometric mediators, bases or oxidizers, leaving groups or elaborated precursors.…”
Section: Methodsmentioning
confidence: 99%
“…General synthetic approaches rely on metal‐assisted catalysis, such as Pd,,, Ni, or Cu catalysts, organic mediators, radical initiators, or photocatalysis‐employing Ir‐complexes . These routes are accompanied by severe disadvantages such as harsh conditions, the necessity for additives or complex ligands, leastwise stoichiometric mediators, bases or oxidizers, leaving groups or elaborated precursors.…”
Section: Methodsmentioning
confidence: 99%
“…[15][16][17] Compound 6, with both benzenesulfonamide and biaryl moieties, was found in our previous study to have remarkable antiproliferative activity. 15 Literature surveys indicate that the N-sulfonyl-aminobiaryl moiety has been comprehensively included in various heterocycles such as carbazole 18 , phenanthridinones, and phenanthridines 19,20 ; but little investigation of its biological potential has been reported., This study therefore, is aimed at synthesis of a series of Nsulfonyl-aminobiaryl derivatives (7-26) and assays of their activity against the growth of cancer cells. In view of the known correlation of microtubule-targeting molecules with inhibition of the STAT3 protein, the synthetic compounds (7-26) have also been examined for their inhibitory activities in tubulin polymerization and STAT3 phosphorylation.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Although the aromatic homologation of 2-phenylphenol was demonstrated under Rh catalysis, the reaction scope was limited to only one example. Our research group has demonstrated palladium-catalyzed C-2'-H activation of N-tosyl-2-aminobiaryls followed by the insertion of [60]fullerene and CO to yield fullerobenzoazepines [11] and phenanthridinones, [12] respectively. CÀH bond activation generally favors C-3-H over C-2'-H in an acidic medium, and knowledge on NHAcdirected C-H activation of C-2'-H on a 2-phenyl moiety is limited to only two examples involving nitro substitution on C-4 or C-5 in moderate yields (Scheme 1d).…”
mentioning
confidence: 99%